1996
DOI: 10.2331/fishsci.62.582
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Seaweed Diets on the Lipid and Fatty Acids of the Japanese Disc Abalone <i>Haliotis discus hannai</i>

Abstract: The effects of seaweed diets on the lipid and fatty acid (FA) composition of juvenile abalone Halio tis discus hannai were investigated by feeding seaweeds with different FA profiles: green (Ulva pertusa, rich in 16:4n-3, 18:3n-3, and 18:4n-3 polyunsaturated fatty acids or PUFAs), red (Grateloupia sparsa, high in 20:4n-6 and 20:5n-3 PUFAs), and brown (Undaria pinnatifida, rich in 18:3n-3, 18:4n-3, 20:4n 6, and 20:5n-3 PUFAs), in a 66-day feeding trial. The best growth was observed in juveniles fed U. pin natif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 8 publications
3
14
1
4
Order By: Relevance
“…The fatty acid composition of all tissues studied from Jade Tiger hybrid abalone generally reflected that of the feeds. This finding is consistent with other studies on abalone 20, 23, 24, 34. Furthermore, our results demonstrated that a considerable amount of FO can be replaced by FlaxO without largely altering the fatty acid profile.…”
Section: Discussionsupporting
confidence: 94%
“…The fatty acid composition of all tissues studied from Jade Tiger hybrid abalone generally reflected that of the feeds. This finding is consistent with other studies on abalone 20, 23, 24, 34. Furthermore, our results demonstrated that a considerable amount of FO can be replaced by FlaxO without largely altering the fatty acid profile.…”
Section: Discussionsupporting
confidence: 94%
“…These results are consistent with the previous studies on the juvenile hybrid abalone (blacklip  greenlip) (Dunstan et al, 1996), and adult blacklip and greenlip abalone (Nichols et al, 1998;Su, Antonas, & Li, 2004, 2006. Studies on other abalone species also showed similar results (Floreto, Teshima, & Koshio, 1996;Hanna & Sinclair, 1996;Nelson et al, 2002). However the contents of these fatty acids are quite different in the three tissue types.…”
Section: Fatty Acid Contentssupporting
confidence: 92%
“…The observed highest growth rate at 396-day old (13-month old) was most likely due to age and macroalgal quality. ), and also fed by H. discus hannai (Ino) (Floreto, Teshima & Koshio 1996). However, the negative growth rate at 608-day old (20-month old) might be due to age, and several other factors like proliferation of nuisance and competitor organisms.…”
Section: Discussionmentioning
confidence: 99%